KOMPETENSI, KOMPENSASI, DAN KEPEMIMPINAN TERHADAP KINERJA KARYAWAN PERSERO DI JAKARTA BARAT - MARIA ULPAH; NURWANTI NURWANTI (Media Bisnis, 2019)
The purpose of this study was to determine the effect of several variables such as, Competence, Compensation, and Leadership to Employee Performance. The object of this research is the regular employees of PT.Pos Indonesia (Persero) West Jakarta. The method used was Descriptive and Simple Regression Method were used to test the hypothesis. Respondents involved in this study were 67 employees. This study uses a purposive sampling method. Data collection techniques by using a questionnaire. The results showed that partially, Competence has effect to Employees Performance, Compensation has effect to Employees Performance, and Leadership has effect to Employees Performance.